Long-term results of medicamentous therapy alone in patients with dilated cardiomyopathy complicated by severe mitral insufficiency - R. V. Buriak; K. V. Rudenko; O. A. Krykunov (Zaporožskij Medicinskij Žurnal)
The aim of this study was to assess survival rates and clinical outcomes in patients with dilated cardiomyopathy (DCM) and severe functional mitral regurgitation (FMR), treated with optimal guideline-directed medical therapy (GDMT).